A Conceptual Framework for Collaborative Development of Intelligent Construction and Building Industrialization - Guo, Zhenxu; Li, Lihong (Frontiers in Environmental Science, 2022)
Digitalization drives the arrival of the era of intelligent construction, which greatly affects the development of construction industrialization. Due to the collaborative barriers between intelligent construction and building industrialization (ICBI), it is difficult for construction enterprises to participate in the actual engineering projects in this work. Achieving the collaborative development of ICBI has become a way to transform and upgrade the construction industry, and it has attracted more and more attention. However, the existing literature lacks consensus on the collaborative development of ICBI affecting the construction industry. In order to promote the theoretical research on the collaborative development of ICBI, this paper proposes a “mi” shaped conceptual framework so that readers can understand the operation law of ICBI collaboration and promote its healthy development. Therefore, based on the synergy theory, this paper extracts the contents of stakeholders’ collaboration, industrial collaboration, structural collaboration, construction technology upgrading, factor endowment upgrading, innovation service upgrading, and construction process upgrading. These seven items are summarized into four dimensions: dual drive, resource supply, collaborative operation, and trust guarantee, which indicate the direction of ICBI collaborative development. The research results will help to realize the industrialization of new buildings and promote the sustainable development of the construction industry.